PERANCANGAN STRATEGI PEMASARAN BERBASIS PERILAKU KONSUMEN DI TOKO SWISS JAYA, JEMBER - Karolina Karolina; Rosita Meitha Surjani; Esti Dwi Rinawiyanti (Perpustakaan Universitas Surabaya, 2013)
Shop Swiss Jaya is engaged in the watch that have been able to dominate the market share of the final consumer in Jember city itself and several retailers who resell to end customers. Business people also required to meet consumer desires so that their existence survive in tough competition with other businesses. Shop Swiss Jaya wants to increase sales volume by more closer to customers to determine the characteristics and desires of consumers. Consumers will be examined are the actual consumers who have purchased the product in the store Swiss Jaya and potential that has not been bought products in store Swiss Jaya. Spread sampling of 160 respondents and 160 respondents actual consumers of potential customers. The analysis was conducted descriptive analysis, crosstabs, MANOVA analysis, quadrant analysis, SWOT analysis, design marketing strategies and marketing mix based STPD 8P. Crosstabs analysis results indicate that there are differences in demographics and consumer behavior between the actual and potential customers. The difference lies in the average expenditure / month (0.000), never satisfied to share the experience of others (0.022), an ordinary wall clock brand purchased (0,011), never heard / knew Swiss Clock Shop Jaya (0.000). While Manova results indicate that there is a difference between the level of importance of actual and potential customers (0.000). While the results of the quadrant analysis shows that the most important variables entered in quadrant IV is the completeness of spare parts, provision of service the product at hand. Variables that are in quadrant IV is in need of repair. Quadrant analysis results are used to perform a SWOT analysis. Proposed marketing strategy for Swiss Stores Jaya by STPD where segemtasinya is based on aspects of human behavior (consumer behavior). Consumer behavior is related to the variables that most consumers in the choice of emphasis at the store to buy the product / service. Actual Consumers Shop Swiss Jaya is most concerned about the variable product watches with an average interest rate of 3.977. As for the potential consumers most concerned about the Physical Evidence variables that have an average interest rate of 3.831. Besides Jaya Swiss Stores segment customers by region and class (upper / middle / lower). The last step is based 8P and calculation of profit with the repair / service products watches